Importance of the indium tin oxide substrate on the quality of self-assembled monolayers formed from organophosphonic acids - Chockalingam, M.; Darwish, Nadim; Le Saux, G.; Gooding, J. (American Chemical Society, 2011)
The role of indium tin oxide (ITO) surface structure and chemistry on the formation of self-assembled monolayers (SAM) derived from organophosphonic acids has been investigated. The surface hydroxide content, crystal structure, and roughness of unmodified ITO surfaces were analyzed with X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), atomic force microscopy (AFM), and contact angle measurements. Organophosphonic acid monolayer modified ITO surfaces were then characterized using electrochemistry, contact angle measurements and impedance spectroscopy. To ascertain the extent of defects, Pb was underpotentially deposited (UPD) onto the monolayer modified ITO surfaces at defect sites and regions where the monolayer was weakly bound. The extent of defects, and the location of defects, in monolayers formed on different ITO surfaces were determined from the amount of charge passed during UPD of Pb at identical conditions, followed by XPS analysis of the Pb 4f peak and imaging with scanning tunnelling microscopy (STM). The results demonstrate that the crystal structure and hydroxide ion concentration of ITO surfaces significantly influence the quality of self-assembled monolayer formation as does the surface roughness. The most well-packed stable monolayers formed only on smooth amorphous ITO substrates with homogeneous grains and high hydroxide content. Lower quality SAMs with significant defects formed on polycrystalline surfaces and the higher the roughness the more the defects. STM defect mapping revealed that the location of defects in monolayers occurred at the boundaries between grain edges on the polycrystalline surfaces. This shows that the substrate characteristics have a strong influence on the quality of monolayers formed on ITO surfaces.